The Rationale Behind Transcirculation Neuroendovascular Interventions: Literature Review Through a Case-Series Approach. Issue 4 (12th April 2023) - Colasurdo, Marco; Edhayan, Gautam; Al Taweel, Alaha; Barghash, Maggie; Kan, Peter; Raghuram, Karthikram
Abstract : BACKGROUND: With the development of advanced endovascular techniques and materials, neurointerventionalists can perform challenging and complex cases that were previously difficult to perform. Transcirculation approaches could be a useful tool used in complicated cases, providing access to the target vessel, through the contralateral or opposite circulation, when anterograde access is difficult or nonachievable. OBJECTIVE: To retrospectively review cerebrovascular interventions performed through a transcirculation approach performed by staff at our Institution. METHODS: English-language studies, published until August 2022, reporting transcirculation interventions in the cerebrovascular circulation were retrospectively collected. Type of intervention, number of cases, rationale, and complications were analyzed. Furthermore, similar cases performed by staff currently at our institution were also reviewed and described. RESULTS: Including our cases, a total of 273 transcirculation treatment approaches have been reported. Intracranial aneurysm embolization, stroke thrombectomies, intra-arterial ophthalmic chemotherapy, arteriovenous malformationss, arteriovenous fistulas embolizations, and intracranial angioplasty and stenting are common indications. Reason for using a retrograde approach were stent/balloon–assisted coiling of wide neck aneurysm in 116 cases, difficult angulation of branch in 91 cases, occlusion of parent vessel in 55 cases, and bailout/other in 11 cases. CONCLUSION: Transcirculation approaches can be considered for cases where conventional anterograde treatment options are not feasible or as a bailout strategy in failed or complicated treatment attempts. They represent a strategy to consider when facing challenging cases, and if performed by experienced and dedicated neurointerventionalists, they can represent a safe alternative.